Peran Bank Indonesia dalam Pengendalian Uang Palsu: Evaluasi Implementasi Kebijakan Hukum di Lampung - Komang Wastawan (CV Rewang Rencang, 2025)
The circulation of counterfeit money threatens economic stability and public confidence in the monetary system. Bank Indonesia plays a strategic role in controlling it through preventive and repressive legal policies. This study analyzes the role of Bank Indonesia and evaluates policies in Lampung using normative juridical methods, a regulatory approach, and secondary data from 2019 to 2023. The results show that despite improvements in currency security features, public education, and law enforcement collaboration, counterfeit currency findings remain fluctuating, peaking in 2021. Key challenges include low literacy levels, limited detection capabilities, and weak coordination. Comprehensive, participatory, data-driven policies are needed to enhance control effectiveness. Conclusion from the results of this article This role is not only technical and administrative but also reflects the legal protection function of the community's economic rights.